The Effect of Egg White Powder Concentration on The Quality of Meatballs Based on Surimi from Tilapia, Catfish and Pangasius - Ferdiansyah; Sara, Dwi; Kelvin; Apriansyah, Miko; Badruzzaman, Falah; Notonegoro, Hartoyo (Journal of Fish Health, 2025)
Surimi is a processed freshwater fish product which is the main raw material for various food products, one of which is fish meatballs. The use of freshwater fish has disadvantages in terms of sensory characteristics, so it is necessary to add other ingredients. One of the additional ingredients that has great potential to affect the characteristics of fish meatball surimi is EWP. This study aims to determine the effect of EWP concentration in surimi from different types of freshwater fish on the characteristics of sensory properties, pH, and yield. The variations in EWP concentration used were 0%; 3% and 6%. Sensory testing included appearance, texture, taste, and aroma. The results showed that appearance, texture, taste and aroma had a significant effect with the best treatment of 0% EWP on catfish and pangasius meatball surimi and 3% EWP on tilapia meatball surimi. The effect of variations in EWP concentration on the pH value of fish meatball surimi did not have a significant effect. The best yield was obtained with the treatment of 6% EWP on each catfish, pangasius and tilapia surimi. The selected catfish and pangasius fish surimi meatballs were 0% EWP concentration while tilapia fish surimi meatballs were 3% EWP concentration because they provided the best meatball quality. The addition of EWP affected the appearance, taste, texture and aroma with the best treatment at a concentration of 3% EWP tilapia fish surimi meatballs and had no significant effect on the pH value, and the best yield at 6% EWP.